2000
DOI: 10.1095/biolreprod62.3.655
|View full text |Cite
|
Sign up to set email alerts
|

A Putative Stimulatory Role of Progesterone Acting via Progesterone Receptors in the Steroidogenic Cells of the Human Corpus Luteum1

Abstract: To further explore the proposed auto-regulatory role of progesterone action in the human corpus luteum (CL), the expression and functional roles of progesterone receptor (PR) isoforms A and B during the luteal phase (LP) of the menstrual cycle were investigated. A total of 27 otherwise healthy patients previously scheduled for surgery were recruited after informed consent. An LH rise was detected, and CL were grouped according to age (Days 2-5 post-LH-rise, early LP; Days 6-10, mid LP; Days 11-14, late LP). Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 45 publications
(64 reference statements)
3
14
0
Order By: Relevance
“…We have confirmed the published observations in women (Iwai et al 1990, Ottander et al 2000, rhesus monkeys (Hild-Petito et al 1988) and baboons (Hild-Petito & Fazleabas 1997) on luteal PR immunostaining. Where PR expression has been quantified there is a clear trend to its reduction in the late-luteal phase in most published studies.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We have confirmed the published observations in women (Iwai et al 1990, Ottander et al 2000, rhesus monkeys (Hild-Petito et al 1988) and baboons (Hild-Petito & Fazleabas 1997) on luteal PR immunostaining. Where PR expression has been quantified there is a clear trend to its reduction in the late-luteal phase in most published studies.…”
Section: Discussionsupporting
confidence: 91%
“…Where PR expression has been quantified there is a clear trend to its reduction in the late-luteal phase in most published studies. This is the case using immunohistochemistry and protein assays in women (Iwai et al 1990, Ottander et al 2000 and immunohistochemistry and Western blotting in non-human primates , Hild-Petito & Fazleabas 1997. Using wellcharacterised human corpora lutea we have confirmed that the PR immunostaining is reduced in the late-luteal phase.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In addition, P has been implicated in the control of tissue inhibitors of metalloproteinase-1 expression in luteinized granulosa cells (78). In humans, it is well known that the CL expresses PR-A and PR-B mRNA, and PR-A was found to be more abundant than PR-B (79,80). Both receptor isoforms decrease in late luteal phase CL.…”
Section: Rescue In a Fertile Cyclementioning
confidence: 99%